STRATEGI SISTEM AUDIT INTERNAL PEMERINTAH DALAM RANGKA TATA KELOLA YANG BAIK - Maliki Heru Santosa; Syamsul Maarif; Eriyatno Eriyatno; Trias Andati (Jurnal Keuangan dan Perbankan, 2016)
The problems related to governance system such as management irregularities or fraud, unaccountable finan-cial practices, and poor public service deliveries have raised some questions to the effectiveness of Units of Government Internal Audit (GIA). The complexity of role and function of GIA, which are both directly and indirectly influenced by the stakeholders and relevant environment, need an appropriate research using sys-temic context. The objective of this study was to identify and establish priority strategy in developing effective internal audit system. This research was based on qualitative approaches with systems methodology which was started with literature study, in-depth interview and focus group discussion (FGD). Then, the study was continued with analytical hierarchy process (AHP) with experts representing the stakeholders. The study showed that to enhance the effectiveness of GIA, it is important to have priority strategy to strengthen the governance system, risk management, and control. The role of the stakeholders and management maturity are the key requirements to successful and an effective of GIA System.